Advances in primate stable isotope ecology—Achievements and future prospects. Issue 10 (18th December 2015) - Crowley, Brooke E.; Reitsema, Laurie J.; Oelze, Vicky M.; Sponheimer, Matt
Abstract : Stable isotope biogeochemistry has been used to investigate foraging ecology in non‐human primates for nearly 30 years. Whereas early studies focused on diet, more recently, isotopic analysis has been used to address a diversity of ecological questions ranging from niche partitioning to nutritional status to variability in life history traits. With this increasing array of applications, stable isotope analysis stands to make major contributions to our understanding of primate behavior and biology. Most notably, isotopic data provide novel insights into primate feeding behaviors that may not otherwise be detectable. This special issue brings together some of the recent advances in this relatively new field. In this introduction to the special issue, we review the state of isotopic applications in primatology and its origins and describe some developing methodological issues, including techniques for analyzing different tissue types, statistical approaches, and isotopic baselines. We then discuss the future directions we envision for the field of primate isotope ecology. Am. J. Primatol. 78:995–1003, 2016. © 2015 Wiley Periodicals, Inc.